An Improved Heuristic Algorithm for UCAV Path Planning. (10th April 2017) - Zhang, Kun; Liu, Peipei; Kong, Weiren; Zou, Jie; Liu, Min
Abstract : The study of unmanned combat aerial vehicle (UCAV) path planning is increasingly important in military and civil field. This paper presents a new mathematical model and an improved heuristic algorithm based on SparseA ⁎ Search (SAS) for UCAV path planning problem. In this paper, flight constrained conditions will be considered to meet the flight restrictions and task demands. With three simulations, the impacts of the model on the algorithms will be investigated, and the effectiveness and the advantages of the model and algorithm will be validated.